Intelligence collection - Clark, Robert M. (SAGE, 2014)
Robert Clark not only explains specific collection systems for analysts, but helps collectors work across boundaries and stovepipes, encouraging them to share collection approaches and to promote cross-pollination of ideas across the collection disciplines. The first part of the book covers open source (OSINT), human intelligence (HUMINT), communications intelligence (COMINT), and cyber collection , while the second part of the book is concerned with signals intelligence (SIGINT), imagery intelligence (IMINT), and others. There is also a chapter devoted to the management of intelligence collection. This full-colour guide is richly illustrated with images and graphics that help readers see examples of each type of collection material.